Varieties of capitalism and growth regimes: The role of income distribution - Jan Behringer; Till van Treeck (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2018)
This article brings together the varieties of capitalism and the growth model approaches to comparative political economy to analyse the macroeconomic implications of changes in income distribution. In the decades before the financial crisis, coordinated market economies (CMEs) and liberal market economies (LMEs) developed different but unsustainable growth models which resulted in global current account imbalances. We analyse the relative importance of wage coordination and income distribution in explaining the emergence of global imbalances. We argue that strongly rising top income shares contributed to the decline in household saving and current account imbalances in major LMEs, whereas pronounced falls in the wage share contributed to the weakness of domestic demand and rising current account balances in CMEs. Wage coordination affected current account imbalances both directly and, more importantly, indirectly through its effects on income distribution. We test the argument for a sample of 18 industrialized countries over the period 1981-2007. – – Dieses Working Paper führt die Forschungsrichtungen der "Varieties of Capitalism" und der "Wachstumsmodelle" in der komparativen politischen Ökonomie zusammen, um die makroökonomischen Auswirkungen von Veränderungen in der Einkommensverteilung zu analysieren. In den Jahrzehnten vor der Finanzkrise entwickelten koordinierte Marktwirtschaften und liberale Marktwirtschaften unterschiedliche, aber nicht nachhaltige Wachstumsmodelle, die zu globalen Leistungsbilanzungleichgewichten führten. Wir analysieren die relative Bedeutung von Lohnkoordinierung und Einkommensverteilung für die Entstehung globaler Ungleichgewichte. Wir argumentieren, dass der starke Anstieg der Topeinkommensanteile in wichtigen liberalen Marktwirtschaften zu einem Rückgang der Sparquote der privaten Haushalte und der Leistungsbilanz beitrug, während der Rückgang der Lohnquote in koordinierten Marktwirtschaften zu einer Schwächung der Binnennachfrage und einem Anstieg der Leistungsbilanz führte. Die Lohnkoordinierung beeinflusste Leistungsbilanzsalden sowohl direkt, aber vor allem indirekt über Effekte auf die Einkommensverteilung. Wir testen das Argument für ein Sample von 18 Industrieländern für den Zeitraum 1981-2007.
urn:nbn:de:101:1-2018102513385603979162
Keywords: 330; Functional income distribution; personal income distribution; wage coordination; varieties of capitalism; growth models